Vitamin D deficiency and subsequent risk of obstructive sleep apnea: a multi-institutional retrospective study - Hung, Kuo-Chuan; Yu, Ting-Sian; Lai, Yi-Chen; Hsu, Chih-Wei; Yew, Ming; Yu, Chia-Hung; Chen, I-Wen (Frontiers in Nutrition, 2025)
BackgroundObstructive sleep apnea (OSA) is a global health concern associated with cardiovascular and metabolic complications. Vitamin D deficiency (VDD) is common and may contribute to OSA pathophysiology; however, most evidence is cross-sectional. This study investigated whether sustained VDD is associated with an increased risk of developing OSA.MethodsThis retrospective cohort study utilized data from the TriNetX federated research network (2010–2023) to investigate the relationship between VDD and incident OSA in adults aged ≥ 18 years. Patients were classified based on sustained serum 25-hydroxyvitamin D levels, with deficiency defined as ≤20 ng/mL and sufficiency as ≥30 ng/mL. To ensure an accurate exposure status, all included individuals underwent confirmatory vitamin D measurements within 3–12 months. After 1:1 propensity score matching, patients were followed for up to 5 years for new-onset OSA diagnoses, with a three-month washout period after vitamin D assessment to mitigate reverse causality and enhance causal inference.ResultsAnalysis of 126,563 matched pairs demonstrated that OSA risk was significantly higher in the VDD group than in the controls (5.7% vs. 4.4%; HR 1.26, 95% CI 1.21–1.30; p < 0.001). This association demonstrated temporal consistency across 1-, 3-, and 5-year follow-ups. A clear dose–response relationship emerged, with severe VDD [≤10 ng/mL] conferring greater risk (HR 1.39, 95% CI 1.26–1.53; p < 0.001). Subgroup analyses revealed significant effect modification: stronger associations in women versus men (HR 1.32 vs. 1.19; P for interaction: 0.003), younger versus older adults (HR 1.45 vs. 1.15; P for interaction <0.001), and overweight/obese versus normal-weight individuals (HR 1.27 vs. 1.02; P for interaction <0.001).ConclusionSustained VDD was independently associated with OSA risk, with temporal consistency and dose–response relationships supporting potential causality. The effects were most pronounced in women, younger adults, and overweight/obese individuals, suggesting that targeted assessment and intervention strategies may be warranted in these high-risk subgroups.